Effects of Oil Extracts of Neem Azadirachta indica A. Juss, Sweetflag Acorus calamus L. on the Rice Weevil Sitophilus Oryzae - Demayo, Cesar; Magallona, Edwin Paul; Barrion, Adelina (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The biochemical effects of neem oil, sweetflag oil and "Margosan-0" on the rice weevil Sitophilus oryzae were investigated by looking at percent mortality and enzyme activity on treated insects. Toxicity results show "Margosan-0'' as the most effective when compared to sweetflag oil and neem oil. Amylase, a- and -esterase activities exhibited a general trend of decreasing enzyme activity in response to increased oil concentration.